Air Sac Nematode ( Serratospiculum tendo) Infection in an Austral Peregrine Falcon ( Falco peregrinus cassini) in Argentina. - Ibarra, Jennifer (2019)
Fil: Ibarra, Jennifer. Fundación Cullunche; Argentina.